POSSIBILITY OF THE MATHEMATICAL MODEL OF COUNTERACTION APPLICATION TO THE ASSESSMENT OF TRANSPORT INFRASTRUCTURE SECURITY LEVEL - A. V. Dormidontov; L. V. Mironova; V. S. Mironov (Научный вестник МГТУ ГА, 2018)
The air transport infrastructure objects security is the state level problem as the part of national and public security of the country. One of the directions in this field is the vulnerability assessment procedure for transport infrastructure objects and on the basis of this procedure the elaboration of ensuring their safety recommendations takes place. The mathematical substantiation of recommendations and their possible implementation is an important part of the marked problem. The possibility of mathematical model of counteraction application, which assesses the offender’s potential and the security’s potential based on evaluative dimensions of the offender and the security system, is under consideration. Assume as a basis the mathematical description model of interaction nature between defender-offender system components, the model known as the competition predator-prey model with quantitative qualitative characteristic parameters of the two systems is taken. The model is modified classical model of Lotka-Volterra competition, which allows us to estimate changes in the danger level formation with reference to the transport infrastructure object and the object security level. The analysis of possible model states is made. The control parameters of the model are described. The mathematical apparatus, which is able to evaluate the danger level, the level of transport infrastructure objects protection, to reveal parameters reducing security system potential and to perform the control parameters data is given. The presented mathematical model identifies the parameters which reduce the security system potential and controls these parameters. The management can be carried out for the purpose of system transfer from one steady state to another, preservation of its operability, increase of its operation cycle and compliance to modern safety requirements. The system of Defender-offender equations correct usage allows us to justify the configurable security system of transport infrastructure objects on the basis of the specified security level.